2008
DOI: 10.1159/000165111
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform Weakness in the Paretic Knee and Compensatory Strength Gains in the Nonparetic Knee Occurs after Stroke

Abstract: Background: This study was designed to quantify torque production at different joint angles in the paretic and nonparetic knee joints of individuals with stroke. Methods: Extension and flexion torques were measured at 6 angles of the knee joint and normalized to peak torque in 19 subjects with stroke and 19 controls. Results: Paretic knee extension torque was lower than controls when the knee was positioned near extension. In contrast, nonparetic knee extension and flexion torques were higher than controls whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
(35 reference statements)
2
15
0
Order By: Relevance
“…Research has shown that improvement of paretic muscle strength prevents overuse of the non-paretic side [16,25] and decreases disability [19,22,26]. In accordance with previous studies [5,6,15,16], placing the paretic leg posterior in this research not only increases activity of the paretic leg, which is suitable for strength-training, but also improves the asymmetrical load condition of StandTS due to the decrease of leg load discrepancy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Research has shown that improvement of paretic muscle strength prevents overuse of the non-paretic side [16,25] and decreases disability [19,22,26]. In accordance with previous studies [5,6,15,16], placing the paretic leg posterior in this research not only increases activity of the paretic leg, which is suitable for strength-training, but also improves the asymmetrical load condition of StandTS due to the decrease of leg load discrepancy.…”
Section: Discussionsupporting
confidence: 85%
“…The clinical significance of asymmetrical leg load during StandTS in connection to sitting impact was not reported. In stroke rehabilitation, training paretic legs in muscle coordination and strength is an important goal [16,20,[24][25][26] since it can prevent the overuse of the non-paretic side through reduced leg load asymmetry. Also, when patients perform daily living activities in various situations where safety considerations are top priority, the use of the non-paretic leg becomes a desirable strategy since the function of the paretic side is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle weakness is characteristic of people following stroke, but greater force deficits are evident when the muscle fibres are shortened. 12,[56][57][58] Force deficits have been observed in a shortened position in the elbow flexors, elbow extensors, knee flexors, and knee extensors 12,57 (see Table 2). It has been suggested that the reason for the deficits in a shortened position 12,56-58 is a preference to use the muscle in the strongest position, halfway between extension and flexion, which results in relative disuse of the muscle in other positions.…”
Section: Angle-torque Relationshipmentioning
confidence: 99%
“…Given that the magnitude of force production is smaller at shorter muscle length in the ascending limb, the slope of EMG-torque relations will become greater at a shorter length, characterized here as the coefficient a in this study. The greater coefficient a on the paretic side can then be explained by an altered active force-length curve after stroke such as narrower width of the curve (19) or by an altered torqueangle curve such as shortened range of the curve (3,(20)(21)(22). Since the reduction in the magnitude of peak forces at shorter muscle lengths becomes greater with a narrower curve width, the slope of EMG-torque relations is likely greater on the paretic side than on the non-paretic side.…”
Section: Effect Of Joint Angle Changes On the Slope Of Emg-torque Relmentioning
confidence: 99%
“…For example, the width of the active force-length curve seems narrower in the paretic medial gastrocnemius (MG) muscles (19) than in the equivalent contralateral muscles. Such altered contractile properties may lead to modified torque-angle curves, showing a significant reduction in the magnitude of the torque at joint angles where muscle length is short (3,(20)(21)(22), potentially resulting in a higher slope of the EMG-torque relation at such a short length. This outcome is likely because the effective torque at shorter lengths is smaller at a given EMG.…”
Section: Introductionmentioning
confidence: 99%